Geografski vidiki poplav v Sloveniji - Komac, Blaž (Geografija Slovenije, 2008)
Slovenia is endangered by floods. Frequent intensive rainfall and heavy rains, a large proportion of mountainous and hilly regions, and numerous populated narrow valley bottoms are the primary reasons for this threat. Floods endanger about seventy thousand hectares of lowlands, and torrential flooding endangers a further three thousand hectares. Due to this enormous threat, Slovenia has more than one hundred years of experience in the field of flood prevention, while only more recently has the awareness developed in the European Union that flood prevention is cheaper in the long run than simply dealing with the consequences of floods. This fact is reflected in the increasing number of laws passed to deal with this danger, and for this purpose maps of flood hazard and flood risk are very important and are presented in the book.